2020
DOI: 10.1021/acsabm.0c00895
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible Single-Unit Resolution All Printed Neural Interface on a Bioresorbable Backbone

Abstract: Neural interfaces are the parts of the neural prosthesis that are in contact with the target tissue. The mechanical, chemical, and electrical properties of these interfaces can be a major determinant of the life of the implant and the neural tissue for chronic and even acute integrations. In this work, we developed a fully inkjet-printed, flexible neural interface on a bioresorbable backbone capable of recording high-fidelity neural activity. We utilized room temperature fabrication processes that overcome the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
(73 reference statements)
2
34
0
Order By: Relevance
“…Figure a shows the EIS of PEDOT-modified microelectrodes with a polymerization charge of 0, 20, 40, 100, 200, 400, and 800 mC/cm 2 , respectively. Impedance spectra similar to those reported from inkjet-printed PEDOT:PSS microelectrodes were obtained from the microelectrodes modified with nanostructured PEDOT coatings, showing a small resistive trend in frequencies less than 100 Hz and a capacitive trend in frequencies more than 100 Hz. Compared to the unmodified microelectrode, the impedance of PEDOT-modified microelectrodes decreases from ∼4 orders of magnitude at low frequency to several ohms at high frequency.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Figure a shows the EIS of PEDOT-modified microelectrodes with a polymerization charge of 0, 20, 40, 100, 200, 400, and 800 mC/cm 2 , respectively. Impedance spectra similar to those reported from inkjet-printed PEDOT:PSS microelectrodes were obtained from the microelectrodes modified with nanostructured PEDOT coatings, showing a small resistive trend in frequencies less than 100 Hz and a capacitive trend in frequencies more than 100 Hz. Compared to the unmodified microelectrode, the impedance of PEDOT-modified microelectrodes decreases from ∼4 orders of magnitude at low frequency to several ohms at high frequency.…”
Section: Resultssupporting
confidence: 67%
“…The impedance value of PEDOT/PF 6 – coatings is much lower than those obtained from conductive polymer coatings created in aqueous solution, , and it is comparable with the that of the nanostructured conducting polymer coatings created with template materials (e.g., PEDOT/CNT composite and PEDOT nanotubes) (Table ). Although a lower impedance was obtained from the PEDOT/PSS prepared from inkjet printing, the simple procedure for the preparation of the nanostructured PEDOT coatings in this study enables its modification on any conductive substrate. The dramatic drop of impedance in this study is presumably due to the greatly enlarged effective surface area.…”
Section: Discussionmentioning
confidence: 99%
“…A recently [28] presented ECoG probe using CNTs on PDMS electrodes exhibits specific capacitance of 1.5 mF/cm 2 , low impedance values of approximately 30 kΩ at 1 kHz and charge storage capacity of 0.35 mC/cm 2 . As a reference, Faradaic silver nanoparticles/PEDOT:PSS (Poly (3,4-ethylenedioxythiophene) Polystyrene Sulfonate) electrodes on polyimide can reach very low impedance value of 200 Ω (at 1 kHz) , exhibit capacitance of 0.4-60.6 mF/cm 2 and charge storage capacity of 1.083 -2.8 C/cm 2 by increasing PEDOT:PSS coating from 1 to 10 layers [29].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…An example of polymers used as a backbone for neural interfaces is polyimide (PI), which is known for its superior thermal and chemical resistance, excellent electrical and thermal insulation of metallic conductors, biocompatibility, and high elasticity ( Khraiche et al, 2017 ). That being said, PI still suffers from a mechanical mismatch with brain tissue due to its high elastic modulus ( Bilston, 2011 ; Almasri et al, 2020 ). Our simulation results ( Figure 10A ) showed that neural probes made of PI will result in a large magnitude reduction of the strain fields (almost two orders of magnitude).…”
Section: Discussionmentioning
confidence: 99%